Calculated of vibrational frequencies for molecular system from sulphur-halides in the infrared region by using the semi empirical programs - Haider Mohammed Jawad Haider (Al-Qadisiyah Journal of Pure Science, 2017)
In this research the molecular composition for non-linear molecular system (S2Cl2) has been studied in the infrared region by using the semi imperial theoretical calculations. Then the semi empirical program for molecular orbits WinMopac7.21 that is using quantum mechanics through MNDO/PM3 method has been used to calculate the total energy at the static molecular geometric composition. And the distance in which the energy has a minimum value which is called the balance distance, It is found that the total energy value for the molecule is (-1005.499 eV) at balance distance (1.84Ã…).Then spectral properties have been studied and calculated to specify the type of composite within the (Mono-halides) group and to study them as a good insulator for electricity and forming stronger types of rubber by process of the rubber Vulcanization (beefing up of rubber)